Implementación del plan de negocio de cevichería mr. pesca'o en la ciudad de Trujillo - Rodriguez Juarez, Diego Agustin (2018)
The present research work describes in detail how Cevichería Mr. Pesca'o was constituted for such a constitution a business plan was prepared. A business plan is a guide for the businessman or entrepreneur. It is a document which describes the business, analyzes the market situation and establishes the actions to be carried out in the future. For the preparation of the business plan, an executive summary, the mission, the vision, the values and the general overview of the company were developed. The executive summary describes the most important aspects of the study. The mission refers to the reason for being Cevichería Mr. Pesca'o, who we are, what we do and for whom we do the activities. The vision is the future situation that we wish to achieve and which has to be a situation achieved over time. The values are the essential principles that should guide the strategic development of Cevichería Mr. Pesca'o, and the general overview of the company refers to the current situation and future plans. It also makes an analysis of the company and its environment through the swot matrix. They also studied topics such as marketing, administration, demand analysis, supply analysis, operations, financial aspects, logistics and legal aspects were developed. With respect to marketing, four P were applied. In administration and human resources the positions of the collaborators and their functions were defined. In the analysis of the demand, a segmentation of this was made. The analysis of the offer was made through the 5 forces of Michael Porter. In operations, a flowchart for the main processes was established. In the financial aspects, the calculation of the initial investment and sales prices were determined. In the logistic aspect, the inputs through the inventory of classification ABC were discriminated, and in the legal aspects, all the documents that cover the legal operation of Cevichería Mr. Pesca'o were stated.